Mechanization Hire-Service Models for Conservation Agriculture in Kenya - Mkomwa, S.; Mutai, W.; Waswa, Boaz Shaban (Bioversity International and the International Center for Tropical Agriculture, 2023)
A study was carried out to profile potential mechanization hire service models in four counties in Kenya. The study profiled 6 models for mechanized hire services in agriculture that can be tapped depending on context of the farmers. These include 1) Individual farmer / entrepreneur service providers, 2) Farmer group/ cooperative service providers, 3) Entrepreneur service providers involved in agricultural activities, 4) Entrepreneur service providers involved in the agricultural mechanization supply chain, 5) Entrepreneurs as intermediary hire service providers, and 6) Government provided service. The most ideal model is individual farmers owning the machinery for their own use and providing services to farmers. The best practical service provision would be small and medium service providers owning several tractors and exclusively providing services to other farmers. Access to mechanization services by smallholder farmers is dependent on the business model linking them to accessing mechanization services.